Effect of processing parameters and heat treatment techniques on foaming properties of aluminium foam developed by friction stir processing route. (February 2023) - Kumar, Mandeep; Raj Singh, Ratnesh Kumar; Jain, Vivek
In the present research friction stir processing has been used to make the precursors. The substrate contains the foamable mixture in a pre-drilled hole and the processing has been done in the centre line of the hole. The developed precursors are then treated by two heating methods, i.e. furnace and microwave heating to produce foam. The effect of different process parameters like the number of friction stir processing passes, volume and composition of foamable mixture, and heat treatment techniques have been investigated. The porous aluminium foam has been found with pore size in the range of 0.24–1.35 mm with a proportion of pores between 41% and 56% with microwave heating, while in case of furnace heating, the pore size is in the range of 0.22–1.49 mm with proportion of pores in between 41% and 61%. Also, the results show that the foam developed in microwave heating is much faster than that of furnace heating.